Research of service quality of hotels in Belgrade by analysis of guest reviews on Facebook - Savović, Nataša; Blešić, Ivana; Tepavčević, Jelena (Turizam, 2023)
The development of the Internet brings with it a significant change, because today users of information do not only depend on the provider of tourist services, but information can also be obtained from other users of these services. The distribution of information is done word-mouth-WOM, but not in a traditional way, but through the use of Web 2.0 applications (eWOM). Hotels’ social media profile are becoming an increasingly important source for consumers when collecting information about hotel products. Social networks make up one network platform for connecting people around the world, enabling them to download information freely through audio-visual, audio and text-based information. Successful communication through social networks today is almost no longer an issue of choice, but is one of the most important tools of business for every hotel and tourist company that contributes to achieving better business results. The aim of this research was to identify if there are differences in perception of service quality in selected hotels. The tested variables were gender and origin of guests and hotel category (number of stars). The results of research showed that there are no differences in perceptions of service quality according to gender and origin of guests. Hotel category proved to be a factor of differences in the perceptions of the guests.